Study of the Vegetation and Fwra of Rajiv Gandm Wildlife Sancruary, Assam - Nath, Surendra Mohan; Chowdhury, S. (Indian Forester, 1994)
Rajiv Gandhi Wildlife Sanctuary, renamed from well know orang Wildlife Sanctuary, situated well within Darrang District with but a small area towards eastern fringe in Sonitpur district of Aasam, lies between 26Â°30’,-26Â°40’ N and 92Â°15’-92Â°30’ E covers an area of nearly 80 km2 A flood plain of River Brahmaputra and its tributary Dhansiri presents a sub-humid tropical area encompassing magnificent man-made forest of indegenous plant species (not less than 50 species) of Assam; natural forested land of deciduous species; savannah; extensive pure grasslands and luxuriant wetlands. An excellent habitat for endangered Rhinoceros unicornis and other wild animals. Based on several field trips conducted since August1991, the authors collected as many as 669 in field numbers to the present, revealed interesting findings not only its vegetation and composition of floristic elements including 45specifies of grasses, 26 species of sedges and a number of ground orchids with 2 new records of species from North-Eastern Region viz., Pecteilis triflora and a peculiar pungent smelling Habenerio graveolen but also on the food habit of particularly Rhinocerous unicornis and Sus scorofa-cristata as well. Besides grasses, most palatable amongst others for Rhios are Equisetum diffusum and E. ramossisimum sub-sp. debile of Fern allies whereas Wildboar even love to devour matured bulbs of ground orchids like species of Geodorum densiflorum, Eulophia and Habeneria etc. A variety of plant resosurces and its impact on growth and development of wiIdlife has also been high-lighted in the paper.